Analisis Persepsi Konsumen Terhadap Produk Cokelat Di Kota Banda Aceh - Nurdiana Sukma; Akhmad Baihaqi (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
ABSTRACT. Chocolate is a food product that is produced from cacao beans (Theobroma cacao L.) that are processed from relatively long several stages. Various chocolate products are very easy to find in the city of Banda Aceh and its brand on the market are very diverse, ranging from international branded products to local brand products, therefore, there was competition between producers in sustaining the market share that has been mastered. Aware of high level of competition among the chocolate products, the manufacturer seeks to introduce its products to the public by showing the various advantages of products attributes that they have. Essentially, marketing stimuli is one of products attributes, which it could affect consumer perception. The purposed of this study is to determine the attributes that influence consumer perception and how consumer perceptions of the chocolate products consumption in Banda Aceh. The method of data analysis using Chi Square Test and descriptive analysis. Based on the result of chi square analysis, the attributes that affect consumer perception is taste, price, quality and advertising. While based on the results of the descriptive qualitative analysis, it turn out that consumers in Banda Aceh have the perception those cocoa products more consumed by the upper classes consumers compared to low income consumers.